The Influence of Principal’s Professional Competence, Work Motivation, and Job Satisfaction on Teachers’ Professional Attitude in Public Elementary Schools in Kejajar District, Wonosobo Regency - Triyono Triyono; Ngurah Ayu Nyoman Murniati; Muhammad Prayito (Ilomata International Journal of Social Science, 2026)
Based on a preliminary assessment conducted in 2024 by the local education supervisory authority under the Wonosobo Regency Education Office, teacher professionalism in public elementary schools in Kejajar District was categorized as low. This classification was based on a standardized monitoring instrument covering pedagogical, professional, social, and personal competencies aligned with the national framework. The assessment of 132 teachers produced an average score of 68.4 out of 100, below the institutional threshold of 75, indicating systemic challenges in maintaining professional standards. This study investigates the influence of principal professional competence, work motivation, and job satisfaction on teachers’ professional attitudes. A quantitative correlational design was applied, involving 125 teachers selected through proportional random sampling. Data were collected using validated Likert-scale questionnaires and analyzed using multiple regression with SPSS version 24. The findings show that principal competence (β = 0.312, p < 0.001), work motivation (β = 0.285, p < 0.001), and job satisfaction (β = 0.267, p < 0.001) each have a positive and significant effect on teachers’ professional attitudes. Collectively, these variables explain 58.6% of the variance (R² = 0.586). These results highlight the integrated role of leadership and motivational factors in shaping teacher professionalism and provide empirical support for strengthening instructional leadership and teacher motivation, particularly in resource-constrained educational contexts. KEYWORDS: Job Satisfaction, Principal’s Professional Competence, Teachers’ Professional Attitude, Work Motivation.